2001
DOI: 10.1515/cclm.2001.020
|View full text |Cite
|
Sign up to set email alerts
|

Free and Complexed Prostate-Specific Antigen (PSA) in the Early Detection of Prostate Cancer

Abstract: We evaluated the analytical performance and diagnostic utility of complexed prostate-specific antigen (CPSA) and their ratios, complexed-to-total PSA (C/T PSA) and free-to-complexed PSA (F/C PSA), in comparison with the total PSA (TPSA) and free-to-total PSA ratio (F/T PSA) as means of diagnosing prostate cancer (PC). Samples (n=101) were drawn from men with no evidence of malignancy (n=80) and from men with PC (n=21) at biopsy. For determination of the F/T PSA ratio, the DPC Immulite-2000 method was used; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Along with digital rectal examination, the PSA test has become part of the routine medical checkup in many countries during the last decades (79) . It is common knowledge that increased preoperative serum PSA levels constitute an independent unfavorable prognostic biomarker in prostate cancer, positively correlating with advanced-stage disease and predicting poor clinical outcome.…”
Section: Malignancies Of the Male Reproductive System Prostate Cancermentioning
confidence: 99%
“…Along with digital rectal examination, the PSA test has become part of the routine medical checkup in many countries during the last decades (79) . It is common knowledge that increased preoperative serum PSA levels constitute an independent unfavorable prognostic biomarker in prostate cancer, positively correlating with advanced-stage disease and predicting poor clinical outcome.…”
Section: Malignancies Of the Male Reproductive System Prostate Cancermentioning
confidence: 99%
“…Although no study has been conclusive, some have shown promising results with an increased specificity over tPSA in the detection of prostate cancer while other studies have shown an equivalence to the f/t PSA. [15][16][17][18][19][20] There also is a cost advantage in using cPSA. In comparison to the measurement of the f/t PSA, which requires two assays, the measurement of cPSA requires only one assay.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed looking at the performance of complexed PSA (cPSA) assays. Although no study has been conclusive, some have shown promising results with an increased specificity over tPSA in the detection of prostate cancer while other studies have shown an equivalence to the f/t PSA 15–20 …”
Section: Introductionmentioning
confidence: 99%